2023
DOI: 10.1126/sciadv.adg7125
|View full text |Cite
|
Sign up to set email alerts
|

TERT accelerates BRAF mutant–induced thyroid cancer dedifferentiation and progression by regulating ribosome biogenesis

Pengcheng Yu,
Ning Qu,
Rui Zhu
et al.

Abstract: TERT reactivation occurs frequently in human malignancies, especially advanced cancers. However, in vivo functions of TERT reactivation in cancer progression and the underlying mechanism are not fully understood. In this study, we expressed TERT and/or active BRAF ( BRAF V600E) specifically in mouse thyroid epithelium. While BRAF V600E alone induced papillary thyroid cancer (PTC), coexpression of BRAF V600E and TERT resulted in poorly diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Another potential link of this risk factor with the invasiveness of the TC could be the length of telomeres and the telomerase activity. Thus, mutations of the gene TERT (i.e., telomerase reverse transcriptase) have been considered impactful on TC cell biology and dedifferentiation [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential link of this risk factor with the invasiveness of the TC could be the length of telomeres and the telomerase activity. Thus, mutations of the gene TERT (i.e., telomerase reverse transcriptase) have been considered impactful on TC cell biology and dedifferentiation [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 The inhibition of rRNA production has been shown to inhibit tumor growth. 10 An inhibitor of RNA polymerase I exhibited antiproliferative activity in cancer cells and tumor xenografts, 1113 further supporting the importance of ribosomal biogenesis for cancer cell population.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies have reported an association between the V600E variant and aggressive disease features such as RAI refractoriness, lymph node metastases, locoregional invasion, and recurrence ( 64 , 67 , 69 ). Interestingly, PTCs with coexisting mutations in BRAF and the telomerase reverse transcriptase (TERT) promoter are associated with aggressive clinicopathological characteristics, more so than either mutation alone ( 70 , 71 ). On the other hand, RAS mutations occur mostly in follicular-variant PTC and non-invasive follicular thyroid neoplasm, which have a genomic profile more similar to FTC.…”
Section: Mutational Landscape Of Tcmentioning
confidence: 99%